[Measuring job satisfaction: construction of a multidimensional investigation tool]: Misurare la soddisfazione lavorativa: costruzione di uno strumento di indagine multidimensionale - Faraci, Palmira; Valenti, Giusy (Giornale Italiano di Medicina del Lavoro ed Ergonomia, 2025)
Background: Although numerous studies have been done on the topic of job satisfaction, as regards the Italian research, the construction of specific psychometric instruments is lacking. Objectives: The present paper is aimed to develop a scale to measure job satisfaction referring to our cultural context. Methods: Participants were 222 workers (36.5% males, 63.5% females) with an average age of 38.39 years (SD = 10.91). The formulated items were selected from a large item pool on the basis of the evaluation by a group of expert judges, and the item analysis procedure. In order to establish test validity, the following instruments were also administered: Occupational Stress Indicator, Satisfaction With Life Scale, Rosenberg Self-Esteem Scale, Multidimensional Scale of Perceived Social Support, and Beck Depression Inventory. Results: Both exploratory and confirmatory factor analyses highlighted a 6-factor structure. Those factors were responsible for 51.30% of the total variance. Reliability analyses indicated satisfying internal consistency (ranging from a = 73 to a = .86). Construct validity was supported by results obtained calculating correlations with the theoretically associated variables. Conclusions: Our findings suggest promising psychometric properties for the presented measure. The instrument could be used in specific programs developed to promote well-being conditions in work settings.